Elaboración de un manual de calidad mediante la aplicación de la normativa de las BPM para el mejoramiento de la producción de chocolate en la Microempresa Chocolates Monge. - Manobanda Zapata, Gabriela Estefanía (2018)
In the present research study, a quality manual was elaborated through the application of Good Manufacturing Practices (GMP) at "Chocolates Monge" micro-enterprise. For the development of the manual, the initial situation of the microenterprise was previously evaluated through a checklist based on the requirements established by the technical sanitary substitute regulation for processed foods, food processing plants, distribution establishments, commercialization, transportation of food and collective food establishments, issued by the Agency for Regulation, Control and Health Surveillance (ARCSA, 2015), through which 8 items were evaluated: facilities, equipment and utensils, workers compliance, raw materials and supplies, operations production, packaging, labeling, transport, marketing, assurance and quality control. Consequently, the following percentage was obtained: 47.6% complies with the current regulations, while 52.4% does not comply. Through the Standardized Operational Procedures (SOP), Standardized Operating Procedures for Sanitation (SOPs) and Critical Control Points (CCP), contamination risks were identified, therefore, preventive and corrective measures were established in the production process. With these tools; safety, is ensured from the entry of the raw material to the distribution of the product to the consumer, optimizing operating costs and improving the quality of their product.